2005
DOI: 10.1111/j.1600-0501.2005.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bone–implant interaction phenomena by using a numerical approach

Abstract: The evaluation of the biomechanical response of implant-bone compound necessarily requires the adoption of accurate numerical models, accounting for the complex geometry of threaded implants, as well as of the anatomy of the patients to be able to provide for reliable results pertaining to stress/strain path on peri-implant bone tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 33 publications
1
45
0
6
Order By: Relevance
“…In this study, the difference in the concentration observed between the microthread and smooth models may act as a bone stimulus [30], since the bone strength acts as a physiological limit. Local overloading in cortical bone occurs in compression when the maximum compressive principal stress exceeds 170-190 MPa in modulus, and in tension when the maximum tensile principal stress exceeds 100-130 MPa [28,32]. In the present study, these stresses were up to 54.6 MPa in compression and 55 MPa in tension.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, the difference in the concentration observed between the microthread and smooth models may act as a bone stimulus [30], since the bone strength acts as a physiological limit. Local overloading in cortical bone occurs in compression when the maximum compressive principal stress exceeds 170-190 MPa in modulus, and in tension when the maximum tensile principal stress exceeds 100-130 MPa [28,32]. In the present study, these stresses were up to 54.6 MPa in compression and 55 MPa in tension.…”
Section: Discussionmentioning
confidence: 68%
“…Excessive occlusal stress can cause bone resorption or even failure of the implant-bone interface, whereas lack of stress may lead to atrophy or even bone loss [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…In the threaded case, 543,116 elements have been required to mesh the implant, 24,640,780 for the cortical bone and 6,272,640 for the trabecular one. 9 The substantial number of elements required to model the threaded implant is significantly higher than that of the smooth implant. This is due to the difficulty of taking the threads into Concerning the smooth configuration, an axial load of 160 N, currently adopted to simulate a classical mastication load [45], is applied with a pressure of 10 MPa on a surface of 16 mm².…”
Section: Characteristics Of the Simulationsmentioning
confidence: 99%
“…A considerable number of experimental and numerical studies have been carried out to understand the mechanism of the load transfer from the implants to the bones [9][10][11][12][13][14][15][16]. A geometric influence has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation